2018
DOI: 10.1038/s41413-018-0039-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes—the enigmatic regulators of bone homeostasis

Abstract: Exosomes are a heterogeneous group of cell-derived membranous structures, which mediate crosstalk interaction between cells. Recent studies have revealed a close relationship between exosomes and bone homeostasis. It is suggested that bone cells can spontaneously secret exosomes containing proteins, lipids and nucleic acids, which then to regulate osteoclastogenesis and osteogenesis. However, the network of regulatory activities of exosomes in bone homeostasis as well as their therapeutic potential in bone inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 170 publications
2
70
0
Order By: Relevance
“…59 To date, cumulative evidence has revealed that exosomes participate in many biological processes, including angiogenesis, cell differentiation, immunomodulation, metabolic balance, and development, 24,26,[60][61][62] and are highly involved in many diseases, such as cancer, neurodegenerative disease, autoimmune diseases, and cardiovascular diseases. [63][64][65][66][67][68][69][70][71][72][73] Recently, the roles of exosomes in bone homeostasis have been extensively addressed. 73 Bone homeostasis is primarily maintained by bone resorption and bone formation, which are involved in various types of cells, including osteoblasts, osteoclasts, osteocytes, and MSCs.…”
Section: Exosomementioning
confidence: 99%
“…59 To date, cumulative evidence has revealed that exosomes participate in many biological processes, including angiogenesis, cell differentiation, immunomodulation, metabolic balance, and development, 24,26,[60][61][62] and are highly involved in many diseases, such as cancer, neurodegenerative disease, autoimmune diseases, and cardiovascular diseases. [63][64][65][66][67][68][69][70][71][72][73] Recently, the roles of exosomes in bone homeostasis have been extensively addressed. 73 Bone homeostasis is primarily maintained by bone resorption and bone formation, which are involved in various types of cells, including osteoblasts, osteoclasts, osteocytes, and MSCs.…”
Section: Exosomementioning
confidence: 99%
“…Fortunately, recent decades witness the conceptual progress of bone biology, which in turn contributes to new therapeutic strategies managing bone loss diseases [3,4]. Bone formation and resorption are viewed as two major events during bone regeneration [5]. Based on this conception, bone anabolic treatments and antiresorption ways were introduced individually [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that exosomal miRNAs may play a vital role in enhancing cartilage regeneration. Extracellular vesicles can be ingested more rapidly by homotypic cells, as opposed to other cells [49]. We believe that the combination of CPC-EVs will serve as excellent "inducing factors" to the repair of clinical OA.…”
Section: Discussionmentioning
confidence: 96%